Effect of sacubitril/valsartan on inflammation and oxidative stress in doxorubicin-induced heart failure model in rabbits - Yu Chun; Li Donghao; Li Zhongyan; Yu Donghui; Zhai Guijuan (Acta Pharmaceutica)
Our study evaluates the effects of sacubitril/valsartan (SAC/VAL) in the rabbit model of doxorubicin-induced heart failure. Twenty rabbits (5 per group) were administered with doxorubicin (DOX, 1.5 mg kg−1, i.v.) to induce heart failure. Specific biomarkers such as BNP, CnT, CRP and ROMs were determined. The cardiac enzymatic anti-oxidant systems were recorded with their electrographic profiles. HR, SBP, DBP and MAP were restored at 5 or 10 mg kg−1 (p.o.) of SAC/VAL compared to DOX, followed by reduced levels of creatinine and BNP (p < 0.001). Significant improvements (p < 0.05) compared to DOX were also noticed in CAT, SOD and LPO with the same doses of SAC/VAL. Specific biomarkers such as BNP, CnT, CRP and ROMs descended significantly (p < 0.001) with treatment when compared to their baseline values. Our findings implied that SAC/VAL treatment reduced the inflammation and oxidative stress to improve the cardiac function.